The Identification Of Visual Character of Traditional Malay and Colonial Architecture at the Seruway Royal Palace in Aceh Tamiang District - Effan Fahrizal; Siti Maysyarah; Armelia Dafrina (Faculty of Engineering, Malikussaleh University, 2018)
Visual character is used to identify and classify type of style in particular building. The growing number of modern buildings causes similarities between one region and another. This results in a loss of people's grip to recognize their own environment and to obscure regional identity. Seruway is one of sub-districts in Aceh Tamiang, in which the majority of the population is Malay ethnic. However, in the colonial period, Malay cultures experienced mixed culture. This mixing occurs in social and architectural life, one of which is the Seruway Royal Palace where there are two styles namely the Malay and colonial architectural styles. This study applied a descriptive qualitative method by identifying the physical elements of buildings that form visual characters covering the upper, wall, and base area with elements of ground plan, style, door and window, roof, ornament, material, color, column, and volume. The results show that the visual character in the Seruway palace that uses Malay architecture lies in material, color, column, door and window. While the colonial architecture applied in ground plan, rooftop ornament, and awning. KEY WORDS: Visual Character, Malay Architecture, Colonial Architecture, Seruway Palace